Media Coverage and Corporate Environmental Disclosure: Evidence from the Yangtze River Delta in China - XIA, Yi (2019)
The corporate social responsibility has been attached increasing importance in the process of the global environmental remediation and the corporate environmental disclosure has been widely regarded as an effective approach to the fulfilment of the corporate social responsibility. Although the corporate environmental disclosure in developed economies has been sufficiently examined since 1970s, the corporate environmental disclosure in China started late and emerged in 2004 and it did not gain much attention until 2008. In particular, prior literature suggests insufficient in-depth studies of the driving factors of the corporate environmental disclosure in China and a little research has paid attention to the effect of the media supervision on environmental disclosure, while many earlier studies have proved the corporate governance and control role played by the media in economic activities. Hence, this dissertation attempted to investigate the relationship between the media coverage and corporate environmental disclosure quality from 2015 to 2017 under a new legal background (ie. new Environmental Protection Law implemented by the MEP in 2015) and further examine the different roles of the media played in firms with divergent ownership structures. The sample was limited in the Yangtze River Delta in order for a more typical and representative result. Combining the legitimacy theory with media agenda-setting theory, this dissertation proposed two hypotheses that the media coverage can play a positive role in facilitating the quality of corporate environmental disclosure and this facilitating effect is more evident for non-state-owned firms. By verifying these hypotheses, a preliminary analysis of the corporate environmental disclosure quality through descriptive statistics by group was conducted, then the fixed-effects panel model was selected to perform the multiple regression analysis in this dissertation. The regression results verified the hypotheses both in the full-sample model and the SOE and non-SOE sub-sample models. The subsequent sensitivity analysis proved the robustness of the results. This dissertation found the following results: First, the media coverage can significantly promote the improvement of corporate environmental disclosure. Second, compared with state-owned firms, the level of environmental disclosure of non-state-owned firms will be affected by the media coverage to a greater extent. This dissertation also provided several implications for policy makers and regulators that the environmental disclosure policy should adapt to the firms and adapt to the economic situation of the region.